Effects of an Educational Intervention on Self-Care and Metabolic Control in Patients With Type II Diabetes - Mahnoush Reisi; Homamodin Javadzede; Gholamreza Sharifirad; Firoozeh Mostafavi; Elahe Tavassoli; Masoumeh Imanzad (Iran University of Medical Sciences, 2017)
Background: Although compliance with all self-care behaviors is necessary for successful management of diabetes, patients with diabetes often refuse favorable self-care. This article is aimed to test the effects of a theory-related intervention to conduce self-aid adherence and metabolic curb in patients having type-2 diabetes.  Methods: In this randomized controlled trial, 80 patients suffering from type-2 diabetes were arbitrarily allotted to intervention and control group. The intervention group attended six sessions in a batch and one-on-one consultation and received an education on self-efficacy and outcome expectations on improving the strategies. Self-efficacy, outcome expectations, self-care behaviors and HbA1c were measured and compared in two groups in the starting, after three and six-months of the interventions. "Intention to treat" analysis was used. Data were analyzed using t test and ANOVA for repeated measures. Results: Mean score of self-efficacy, outcome expectations and self-care behaviors revealed significant differences between two groups in the results of three and six months after the intervention (P < 0.01). A major fall in HbA1c was noted in the intervention group. The mean scores of the HbA1c showed a significant difference between two groups, six months after the intervention (P < 0.05). After the intervention diet, physical activity and foot care improved significantly in the intervention group (P < 0.001). No significant improvement occurred in self-monitoring of blood glucose and medication adherence between two groups after the intervention Conclusion: It is concluded that implementing educational interventions based on the self-efficacy model and related strategies can be effective for patients with type-2 diabetes and is recommended to be used for patient education in the field of metabolic control.